Effect of real-world fear on risky decision-making in medical school-based students: A quasi-experimental study - Wang, Lei; Chen, Sheng; Xiao, Wei (Frontiers in Behavioral Neuroscience, 2023)
Objective:To explore the effect of real-world fear on risk decision-making under certainty and uncertainty. Methods: This quasi-experimental study enrolled non-psychology undergraduates volunteers from the Preventive Medical institute medical school in Xi’an between 17 and 20 years old. Participants were randomly divided into two groups, andeach group received a two-stage crossover design intervention (calm and fear situations) and completed the tasks of risky decision-making under uncertainty (balloon analog risk task, BART) and certainty (Cambridge gambling task, CGT), respectively.The primary outcomes included the behavioral impulsivity measured by the BART value, and the speed of decision making, quality of decisions, adventure index, behavioral impulsivity and risk adjustment measured by CGT. The secondary outcome was the concentration of cortisol in the saliva. Results: A total of 60 questionnaires and data were obtained from 60 participants (28 males and 32 females, aged 19.55 ± 0.75). Compared with in calm situation, participants were more likely to have lower BART value (p = 0.013), slower speed of decision making (p < 0.05), and higher adventure index (p = 0.018) in fear situation. While, the quality of decisions (p = 0.189), behavioral impulsivity index (p = 0.182), and risk-adjustment (p = 0.063) between subjects in fear and calm situation were comparable. Furthermore, the mean value of adventure index of CGT in male subjects was significantly higher than that in female subjects (p < 0.05), and the cortisol concentration in saliva at the fear situation were significantly higher compared to the calm situation (p < 0.05). Conclusion: Fear might reduce the behavioral impulsivity under uncertainty, and increase the adventure index under certainty in risky decision-making. Risky behavior might be influenced by gender Under certainy in risky decision-making, men are more adventurous. Additionally, fear increases the secretion of the cortisol in saliva.